IBM z13 technical introduction - Lascu, Octavian; Bakker, Erik; Eckam, Hans-Peter; Hamid, Parwez; Krishnakumar, Rakesh; LaFalce, Steven; Neto, Lourenço Luitgards Moura; Nogueira, Mauricio Andozia; Packheiser, Frank; Palacio, Ewerson; Rodolfi, Giancarlo; Spahni, André (IBM Corporation, International Technical Support Organization, 2015)
This IBM® Redbooks® publication introduces the IBM z13™. IBM z13 delivers a data and transaction system reinvented as a system of insight for digital business. IBM z Systems™ leadership is extended with these features: Improved ability to meet service level agreements with new processor chip technology that includes simultaneous multithreading, analytical vector processing, redesigned and larger cache, and enhanced accelerators for hardware compression and cryptography Better availability and more efficient use of critical data with up to 10 TB available redundant array of independent memory (RAIM) Validation of transactions, management, and assignment of business priority for SAN devices through updates to the I/O subsystem Continued management of heterogeneous workloads with IBM z BladeCenter Extension (zBX) Model 004 and IBM z Unified Resource Manager This Redbooks publication can help you become familiar with the z Systems platform, and understand how the platform can help integrate data, transactions, and insight for faster and more accurate business decisions. This book explains how, with innovations and traditional strengths, IBM z13 can play an essential role in today's IT environments, and satisfy the demands for cloud deployments, analytics, mobile, and social applications in a trustful, reliable, and secure environment with operations that lessen business risk.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed April 6, 2015)
Keywords: Storage area networks (Computer networks); Computer network architectures; Information storage and retrieval systems; Information Systems; Réseaux de stockage (Informatique); Réseaux d'ordinateurs; Architectures; Systèmes d'information